Dosage analysis of the 7q11.23 Williams region identifies BAZ1B as a major human gene patterning the modern human face and underlying self-domestication - Zanella, Matteo; Laugsch, Magdalena (Science advances, 2019)
We undertook a functional dissection of chromatin remodeler BAZ1B in neural crest (NC) stem cells (NCSCs) from a uniquely informative cohort of typical and atypical patients harboring 7q11.23 copy number variants. Our results reveal a key contribution of BAZ1B to NCSC in vitro induction and migration, coupled with a crucial involvement in NC-specific transcriptional circuits and distal regulation. By intersecting our experimental data with new paleogenetic analyses comparing modern and archaic humans, we found a modern-specific enrichment for regulatory changes both in BAZ1B and its experimentally defined downstream targets, thereby providing the first empirical validation of the human self-domestication hypothesis and positioning BAZ1B as a master regulator of the modern human face. In so doing, we provide experimental evidence that the craniofacial and cognitive/behavioral phenotypes caused by alterations of the Williams-Beuren syndrome critical region can serve as a powerful entry point into the evolution of the modern human face and prosociality. - Dissecting the BAZ1B genetic circuitry in the neural crest brings out its critical role in shaping the modern human face. - Dissecting the BAZ1B genetic circuitry in the neural crest brings out its critical role in shaping the modern human face.
Gesehen am 24.01.2020